The Relationship between Online Learning and Student Stress Levels During the Covid-19 Pandemic at Klakah Senior High School. Thesis, Bachelor Nursing Program, Hafshawaty Institute of Health Sciences Zainul Hasan Genggong - Zakiyah Muslimah; Rizka Yunita; Suhari Suhari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Online learning is a learning method that is carried out to students through communication that is carried out without face to face or online. Online learning is one of the alternatives carried out by teachers so that they can continue to carry out online learning activities for students which are carried out as a result of the corona outbreak that occurred in Indonesia. The purpose of this study was to determine the relationship between online learning and student stress levels during the Covid-19 pandemic at Klakah Senior High School. This type of research is a quantitative type with a cross sectional study approach. Data was taken by giving questionnaires and observing on July 2021 with a sample of 217 respondents using the Simple Random Sampling technique. By analysis using Spearman Rank. From the results of the identification of variables, it was found that most of the respondents had good online learning categories as many as 152 respondents (70%) and most of the respondents had stress levels in the non-stress or normal category as many as 150 respondents (69.1%). From the test results using the Spearman's rho test, it was found that the value of p < 0.05, namely p = 0.000, which means that there is an analysis of the relationship between online learning and the stress level of students during the Covid-19 pandemic at Klakah Senior High School. The results of the research are expected to be input for the school to create programs or forums for students to assist students in conveying the difficulties experienced during online learning.